Conditioning of root canal anatomy on static and dynamics of nickel-titanium rotary instruments - Italo Di Giuseppe; Davide Di Giuseppe; Vito Antonio Malagnino; Enrico Paolo Silla; Francesco Somma (Ariesdue, 2015)
Aim: Aim of this study is to analyze the real movement, influenced by anatomical difficulties, of nickel-titanium rotary instruments within root canal systems; then the objective is to point out the physical and geometrical characteristics of an ideal instrument, able to overcome the most complex anatomies. Methodology: At first, observation of the behavior of nickel-titanium rotary instruments within root canal systems and of the influence on them of root canal anatomy. Then, attempt to avoid the anatomical obstructions exploiting, with manual rotation, the advantages of a zero/low torque. Results: Given that, in some root canals the severity of the curves prevents instruments to advance in rotation, we obtained significant results by manually advancing and rotating NiTi rotary instruments. Conclusions: Therefore, in some cases, we would need an instrument that can reconcile efficiency with a reduction of mass and torque; the ideal instrument should have a very contained working part, combining efficiency with the decrease of mass and, consequently, of torsional stresses too.